A three year review of Tuberculosis surveillance data in Montserrado County, Liberia, 2016-2018 - Alberta Berlynda Corvah; Himiede Wilson Sesay; Delia Akosua Bando; Patrick Konwloh; Benedict Calys-Tagoe; Ernest Kenu (Journal of Interventional Epidemiology and Public Health)
Introduction: Tuberculosis (TB) is a public health problem. Liberia's annual mortality rate remains high with estimated incidence 14,000 cases (308 per 100,000). The study's objective was to analyze the distribution of TB cases by person place and time, estimate the prevalence, case detection rate and outcome of all form of TB cases in Montserrado from 2016-2018.